1986
DOI: 10.1099/0022-1317-67-10-2267
|View full text |Cite
|
Sign up to set email alerts
|

Acyclovir Efficiently Inhibits Oropharyngeal Excretion of Epstein-Barr Virus in Patients with Acute Infectious Mononucleosis

Abstract: SUMMARYShedding of Epstein-Barr virus (EBV) into saliva was studied in 31 patients with verified acute infectious mononucleosis. The patients had been randomized for intravenous treatment with acyclovir (ACV) at 10 mg/kg body weight at 8 h intervals for 7 days, or placebo, in a double-blind trial. EBV in centrifuged throat washings was detected by transformation of umbilical cord lymphocytes and by immunofluorescence staining for EBV-associated nuclear antigen in fixed cell smears. Saliva samples were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 19 publications
(10 reference statements)
0
19
0
Order By: Relevance
“…Acyclovir antiviral activity against EBV was also reported in vitro (Long et al 2003). Some studies have shown that acyclovir combined with prednisolone inhibits replication of oropharyngeal EBV without affecting the duration of IM clinical symptoms (Ernberg and Andersson 1986;Tynell et al 1996). However, no studies have yet reported clinical data indicating that acyclovir is effective in the treatment of EBV-IM and IM-like illness in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Acyclovir antiviral activity against EBV was also reported in vitro (Long et al 2003). Some studies have shown that acyclovir combined with prednisolone inhibits replication of oropharyngeal EBV without affecting the duration of IM clinical symptoms (Ernberg and Andersson 1986;Tynell et al 1996). However, no studies have yet reported clinical data indicating that acyclovir is effective in the treatment of EBV-IM and IM-like illness in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Second, treatment of latently infected individuals with long term acyclovir eliminates virus excretion but does not aVect the level of latent infection in B cells. 11 When treatment is stopped, the virus can be detected in the oropharyngeal secretions at pretreatment levels. 12 Third, studies of EBV strains in donor-recipient pairs before and after bone marrow transplantation have shown that the recipient's strain disappears from the oropharynx and is replaced by the donor's strain.…”
Section: The Natural History Of Ebv Infectionmentioning
confidence: 99%
“…Growing cells were harvested from their wells and the resulting LCLs were expanded. EBV was also recovered from mouthwashes of patient 1, her husband, and patient'2's donor by using the cord blood cell transformation assay (22). EiIV Serology.…”
Section: Methodsmentioning
confidence: 99%